2017
DOI: 10.1177/1060028017706977
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness and Safety Analysis of Dual Antiplatelet Therapies Within an Integrated Delivery System

Abstract: Dual antiplatelet therapies differed in both MACE and bleeds in a real-world setting of PCI. Prasugrel was associated with fewer MACE, whereas clopidogrel had fewer major bleeding events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…For example, Larmore et al found that major adverse cardiovascular and major bleeding events were lower at 30‐days in the prasugrel‐treated group when compared to the ticagrelor‐treated group in patients with ACS treated with PCI 18 . However, most observational studies found no significant difference in the incidence of adverse cardiovascular and bleeding events when comparing ticagrelor and prasugrel in patients with ACS 7–11 . Our ITT sensitivity analysis provided results that were consistent with recent observational studies evaluating prasugrel and ticagrelor and that were contrary to the findings from the ISAR‐REACT 5 trial.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…For example, Larmore et al found that major adverse cardiovascular and major bleeding events were lower at 30‐days in the prasugrel‐treated group when compared to the ticagrelor‐treated group in patients with ACS treated with PCI 18 . However, most observational studies found no significant difference in the incidence of adverse cardiovascular and bleeding events when comparing ticagrelor and prasugrel in patients with ACS 7–11 . Our ITT sensitivity analysis provided results that were consistent with recent observational studies evaluating prasugrel and ticagrelor and that were contrary to the findings from the ISAR‐REACT 5 trial.…”
Section: Discussionsupporting
confidence: 85%
“…The observational literature evaluating outcomes of antiplatelet use in patients with ACS undergoing PCI has shown conflicting results 5–9,18,28 . Differences in how study designs address variability in follow‐up time, inclusion, and exclusion criteria, approaches for addressing covariates may lead to divergent conclusions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two manuscripts were published in peer-reviewed journals and four others were either under review or in the manuscript development phase as of fall 2019. 10,11…”
Section: Resultsmentioning
confidence: 99%
“…Taking ticagrelor as example, the landmark trial PLATO demonstrated that ticagrelor, compared to clopidogrel, reduced MACE (HR 0.84, 95% CI 0.77–0.92), MI (HR 0.84, 95% CI 0.75–0.95), vascular death (HR 0.79, 95% CI 0.69–0.91) and all‐cause death (HR 0.78, 95% CI 0.69–0.89) at 1 year 6 . Coons et al reported in a study of 8127 post‐PCI subjects that ticagrelor did not show reduced MACE compared to clopidogrel (HR 1.05, 95% CI 0.52–2.13) at 1 year 11 . A comparative observational study in Greece using Greek antiplatelet (GRAPE) registry showed only reduction of all‐cause death using prasugrel/ticagrelor compared to clopidogrel at 1 year (HR 0.61, 95% CI 0.38–0.98), but not MI (HR 0.65, 95% CI 0.27–1.57) or stroke (HR 1.03, 95% CI 0.53–2.00) 12 .…”
Section: Discussionmentioning
confidence: 99%